Acute oedema in the evaluation of microvascular reperfusion and myocardial salvage in reperfused myocardial infarction with cardiac magnetic resonance imaging - Arintaya Phrommintikul (2018)
The accurate measurement of myocardial salvage is critical to the ongoing refinement of reperfusion strategies in acute myocardial infarction (AMI). Cardiac magnetic resonance imaging (CMR) can define the area at risk in AMI by the presence of myocardial oedema, identified by high signal intensity on T2-weighted imaging with a short inversion time inversion-recovery (STIR) sequence. In addition, myocardial necrosis can be identified with CMR delayed contrast enhanced imaging. In this prospective study we examined the relationship of acute oedema and necrosis with impaired microvascular reperfusion. We also evaluated acute oedema as a marker of the area at risk in AMI, for the purposes of documenting myocardial salvage. CMR was performed on 15 patients with (AMI), within 24 h of successful percutaneous coronary intervention (PCI). Left ventricular (LV) systolic dysfunction was defined by a systolic thickening <40% (severe <20%). Microvascular reperfusion was evaluated during the acute phase of contrast wash-in. CMR was repeated 3 months post-PCI to evaluate recovery of LV function and final infarct size. Myocardial salvage was defined as the percentage of the area at risk that was not infarcted on follow up CMR. There was a significant correlation between impaired microvascular reperfusion and the extent of segmental oedema (R = 0.363, P < 0.01), but not myocardial necrosis (R = 0.110, P > 0.5). The extent of myocardial salvage correlated with recovery of systolic function (R = 0.241, P < 0.05), which was strongest in LV segments with severely reduced systolic function (R = 0.422, P < 0.01). Conclusions: In acutely reperfused AMI, oedema can be used to identify the area at risk for the purpose of calculating myocardial salvage. The correlation between myocardial oedema and reperfusion status suggests a pathological role of acute oedema in the impairment of microvascular reperfusion. © 2009 Elsevier Ireland Ltd. All rights reserved.